2002
DOI: 10.1046/j.1360-0443.97.s01.2.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cannabis Youth Treatment (CYT) experiment: rationale, study design and analysis plans

Abstract: The feasibility of implementing the CYT manual-guided treatment and quality assurance model in community-based adolescent treatment programs is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
202
1
16

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(222 citation statements)
references
References 79 publications
3
202
1
16
Order By: Relevance
“…41 Teens appear to report more misbehaviors than their parents report for them and to self-report more marijuana use than is detected in urinalysis. 42 Although the study is limited in its relatively brief follow-up period, it is first important to establish an effect of treatment, and then to determine if it can be extended. Future investigations should include longer followup periods.…”
Section: Discussionmentioning
confidence: 99%
“…41 Teens appear to report more misbehaviors than their parents report for them and to self-report more marijuana use than is detected in urinalysis. 42 Although the study is limited in its relatively brief follow-up period, it is first important to establish an effect of treatment, and then to determine if it can be extended. Future investigations should include longer followup periods.…”
Section: Discussionmentioning
confidence: 99%
“…Five published studies were identified: Matching Alcohol Treatment to Client Heterogeneity, (MATCH) ( Project MATCH Research Group, 1997;Project MATCH Research Group, 1993); The Cannabis Youth Treatment Study (Cannabis Youth) (Dennis et al, 2004;Dennis et al, 2002); NIDA Collaborative Cocaine Treatment Study (Cocaine Collaborative) (Crits-Christoph et al, 1997;Crits-Christoph et al, 1999); Project COMBINE (COMBINE) (COMBINE Study Research Group, 2003); and the United Kingdom Alcohol Treatment Trial, (UKATT) (Team., 2005;UKATT Research Team, 2001). Additionally, we reviewed seven multi-site studies conducted within the NIDA CTN: Motivational Interviewing/Motivational Enhancement Therapy (MI/MET) (Carroll et al, 2006); HIV Risk Reduction During Detoxification (HIV-Detox) (Booth, 2005); Concurrent Treatment for Women with Trauma (Women and Trauma) (Hein, 2006); Smoking Cessation Treatment with Transdermal Nicotine Replacement Therapy in Substance Abuse Rehabilitation Programs (Smoking Cessation) (Reid, 2004); Job Seeker Training (Job Seekers) (Svikis, 2003); Safer Sex Skills for Women and Men (Safe Sex Skills) (Tross, 2005), (Calsyn, 2004); Brief Strategic Family Therapy (BSFT) (Szapocznik, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Intake data from two projects was used to create the short comorbidity scales: the Cannabis Youth Treatment (CYT) project 23,24 and the Early Re-Intervention (ERI) project. 8,25 These studies were chosen to represent heterogeneous subsamples (differing in age, race, gender, substance use pattern, comorbidity, and level of care) to evaluate the robustness of the relationship between the short comorbidity and full-length scales.…”
Section: Methodsmentioning
confidence: 99%
“…The scales are also highly correlated with measures of use from timeline follow-back measures, urine tests, collateral reports, treatment records, and blind psychiatric diagnosis (rho of 0.70 or more; kappa of 0.60 or more). 8,23,24,26,29,30 Confirmatory factor analyses suggest that the GAIN's collection of psychiatric and behavioral problems items vary largely along four dimensions: (1) substance use problems (e.g., abuse, dependence, induced), (2) internalizing problems (e.g., depression, anxiety, trauma, suicide), (3) externalizing problems (e.g., attention deficit, hyperactivity/impulsivity, conduct disorders), and (4) crime and violence (e.g., interpersonal, oral, and physical violence, property crime, drug related crime, violent crime; CFI=0.92, RMSE=0.06). 31 In this paper, we focus only on the non-substance use scales.…”
Section: Data Sourcementioning
confidence: 99%